2001
DOI: 10.1029/2000gl011884
|View full text |Cite
|
Sign up to set email alerts
|

Traveling ionospheric disturbances detected in the FRONT Campaign

Abstract: high-latitudes to low-latitudes. The significant coincidence between the structures of 630 nm band airglow and total electron content indicates that the perturbations take place in the bottomside of the ionospheric F region. Coherent echoes from the field-aligned irregularities were observed by the MU radar in the nights when the TID activity was high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
156
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(162 citation statements)
references
References 14 publications
6
156
0
Order By: Relevance
“…Therefore, the time delay between the appearance of Es and QF does not necessarily represent the time required for the establishment of the instability that causes the spread-F development. In this regard, Yokoyama et al (2009) reported that during the most favorable condition, the coupled EsPerkins instability takes 700 s (∼ 12 min) to generate variations sufficient to account for the observed airglow and GPS-TEC perturbations by Saito et al (2001). Thus, the foEs averaged during a 1 h interval before QF may have little correlation with QF.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the time delay between the appearance of Es and QF does not necessarily represent the time required for the establishment of the instability that causes the spread-F development. In this regard, Yokoyama et al (2009) reported that during the most favorable condition, the coupled EsPerkins instability takes 700 s (∼ 12 min) to generate variations sufficient to account for the observed airglow and GPS-TEC perturbations by Saito et al (2001). Thus, the foEs averaged during a 1 h interval before QF may have little correlation with QF.…”
Section: Discussionmentioning
confidence: 99%
“…This dense distribution of GPS receivers is suitable to study spatial structures and the temporal evolution of TEC perturbations in detail. The high resolution TEC maps over Japan have been derived with GEONET data since 1997 (Saito et al, 1998(Saito et al, , 2001. Otsuka et al (2002) developed a new technique to derive the absolute values of vertical TEC, in which a weighted least-squares fitting is used to determine unknown instrumental biases, assuming that the hourly TEC average is uniform within an area covered by a GPS receiver.…”
Section: Observations and Methods Of Analysismentioning
confidence: 99%
“…All sky images (e.g. Garcia et al, 2000;Kubota et al, 2001;Saito et al, 2001;Shiokawa et al, 2003) and GPS time delay (e.g. Saito et al, 1998;Tsugawa et al, 2007) show nighttime F layer structure with a clear statistical tendency to form fronts elongated from northwest to southeast (Northern Hemisphere), and generally propagating to the southwest.…”
Section: Introductionmentioning
confidence: 99%